2017
DOI: 10.6002/ect.2014.0283
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Infections are Achilles heel of kidney transplant recipients. Opportunistic fungal infections are increasingly recognized in these patients. We report a case of kidney transplant recipient with skin and soft tissue infection caused by Pyrenochaeta romeroi, a dematiaceous fungi. Infection by this organism is rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Medicopsis romeroi is an emerging fungus causing subcutaneous phaeohyphomycosis. It has mostly been reported in immunocompromised patients receiving immunosuppressive drugs for hematologic malignancy [4], renal transplantation [5], rheumatoid arthritis [6], leprosy [7], and asthma [8]; however, there has been one report of a healthy, immunocompetent host [11], as shown in Table 2. Medicopsis romeroi has also reported in patients with type 2 diabetes mellitus who have poor glycemic control [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medicopsis romeroi is an emerging fungus causing subcutaneous phaeohyphomycosis. It has mostly been reported in immunocompromised patients receiving immunosuppressive drugs for hematologic malignancy [4], renal transplantation [5], rheumatoid arthritis [6], leprosy [7], and asthma [8]; however, there has been one report of a healthy, immunocompetent host [11], as shown in Table 2. Medicopsis romeroi has also reported in patients with type 2 diabetes mellitus who have poor glycemic control [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Medicopsis romeroi is an emerging fungus causing subcutaneous phaeohyphomycosis. Recent case reports have demonstrated that most patients with subcutaneous phaeohyphomycosis arising from Medicopsis romeroi have impaired immune systems [[4], [5], [6], [7], [8]], including patients with type 2 diabetes mellitus who have poor glycemic control [9,10]. Total surgical excision and debridement are the other options for eradicating the infection [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…These 52 cases corresponded to 38 cases of PHM, including ours [ 1 , 2 , 3 , 4 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] and 14 cases of eumycetoma [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Two cases published as mycetoma by Thiyagarajan et al and Sum et al [ 20 , 21 ] were classified in this review as PHM, regarding the clinical presentation and the lack of grains and bone involvement.…”
Section: Methodsmentioning
confidence: 82%
“…One of them was cured only by surgery [ 25 ], and another one by a combination of surgery and antifungal treatment [ 26 ]. One case showed a progression despite antifungal treatment [ 27 ], while no outcome was available for the last one [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation